World Conference on the International Islamic Calendar - Mohammad Ilyas (International Institute of Islamic Thought, 1992)
The University of Science Malaysia, Penang, Malaysia, and the Organization of Islamic Confetence’s Standing Committee on Scientific and Technological Cooperation (COMSTECH), tecently otganized and hosted the World Conference on the Intemational Islamic Calendar. The theme, “Towads a Unified World Islamic Calendar,” was discussed during eight sessions by an international audience consisting of about two hundred dignitaries, ulama, policymakers, scientists, and professionals from twenty-five countries and ten major international organizations. It was also genemusly sponsored by fifteen other agencies, including the Intemational Institute of Islamic Thought (IIIT). The conference was opened by Tun Dato’ Sen Haji Hamdan Sheikh Tahit, head of the State of Penang. This matked the initiation of the systematic implementation process for the intemational Islamic calendar. Dato’ Haji Musa Mohammad, vice Chancellor of the University of Science Malaysia and conference chainnan, thanked the planners in his welcoming address. He was followed by M. A. Kazi and Ambassador M. Mohsin, who addressed the confetence on behalf of COMSTECH and OIC respectively. Kazi stressed the importance of developing a uniform and systematic intemtional Islamic lunar calendar through continued and detailed study by those qualified to do so. Ambassador Mohsin pointed out the need to unify the existing calendars in the Muslim world. The OIC, he said, is in the process of making this a regular priority item in its agenda and is ready to give its full support. The keynote addtess, “Internationalizing the Islamic Calendar: The Challenge of a New Centuty,” was delivered by Mohammad Ilyas. He highlighted some of the work that had gone into developing the calendar program, explained what progress has been made on predicting the new moon’s visibility, and related how this can be used for an international Islamic calendar. He also focused on the interrelation of science, the Shari‘ah, and policy and its implication for the question of implementation. The conference also heard reports from members in Australia, Nigeria, Tanzania, the United States, Egypt, Itan, Jordan, Morocco, Saudi Arabia, Turkey, Bangladesh, India, Pakistan, Sri Lanka, Brunei, Indonesia, Malaysia, ...